Vocational High School Students’ Perception in learning English and Its Relation to their Career Aspiration in Yogyakarta - Nana Apriliana; Basikin Basikin (Makassar State University, 2021)
Abstract. In Indonesia, Vocational High Schools (VHSs) are designed to prepare graduates for a specific job. Selecting the types of English that suits the needs of vocational students is paramount importance to support their vocational skill in the ASEAN Economic Community (AEC). This study aims to reveal: (1) Vocational High School (VHS) students’ English perceived needs, (2) VHS students’ career aspirations toward study program they are taking, (3) the effect of students’ perception of their English program (EGP and ESP) on their career aspirations, and (4) the differences in the students’ perception of their English program (EGP and ESP) by demographic variables (gender and study program). This was quantitative research in the form of a correlational study. The data were analyzed using descriptive analysis, multiple regression, and multivariate analysis of variance (MANOVA). The findings indicated that: (1) Most VHS students' English perceived need was ESP. Nevertheless, it was also undeniable that they also still needed EGP for their English before they took ESP. (2) Most VHS students did not have mature career aspirations related to the study program they were taking at vocational high school. (3) Furthermore, there was a significant effect of students' perception (EGP and ESP) on their career aspirations. (4) Regarding differences between male and female's perception of English program and differences in students’ study program, the results of this study revealed significant differences among them. Keywords: Career Aspiration, EGP, ESP, Perception